DILEMA PRIORITAS KURIKULUM UMUM DI LINGKUNGAN PESANTREN TARBIATUSSHIBYAN (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
Islamic boarding schools in Indonesia face a dilemma in determining priorities between the pesantren curriculum and the general curriculum. This study aims to examine the practice of curriculum integration and its implications for the learning process at Tarbiatusshibyan Islamic Boarding School. A descriptive qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participatory observation, and curriculum document analysis. The findings indicate that curriculum integration at Tarbiatusshibyan remains parallel and structural rather than conceptual. Limited time allocation, dense student activities, and differing evaluation systems contribute to the tension between deep classical Islamic text instruction and the fulfillment of general curriculum demands. This study recommends the development of a contextual and systematic curriculum integration model to ensure that pesantren education maintains its Islamic character while remaining responsive to national educational standards.